COVID-19 and oral cavity - repercussions and post-vaccination care: a clinical case (Research, Society and Development, 2022)
Adverse event descriptions such as rare thromboses with concomitant thrombocytopenia, including venous thromboses at unusual sites such as cerebral venous sinus thrombosis (CVST), intestinal venous and arterial thromboses, have been reported following vaccination for COVID-19 based on recombinant adenoviral vector. The emergence of clinical features of moderate to severe thrombocytopenia and thrombotic complications, increasing fibrin formation in different parts of the body, approximately 1 to 2 weeks after vaccination against SARS-CoV-2 suggests a disorder that clinically resembles clinical presentations of long-term use of heparin. The case report consists of paroxysmal left-sided hemicrania after local vaccination protocol, in addition, the patient presents areas of retraction and papillary necrosis, hyperplastic regions with bleeding, not consistent with periodontal diseases associated with biofilm, during the physical examination. The possibility of ischemic stroke in vaccinated people as well as in patients with COVID-19 justifies the therapeutic and prophylactic use of anticoagulants, increasing post-vaccination safety. Although the phenomena related to thromboembolic complications induced by the vaccine for COVID-19 are rare, a careful evaluation including specific laboratory tests and a correct systemic diagnosis is necessary. In addition, the observation of certain pathologies caused by thrombus formation in the oral cavity can help in the preventive identification of vaccine-induced thrombotic thrombocytopenia (VITT).